Large scale genome reconstructions illuminate Wolbachia evolution - Scholz, Matthias (Nat Commun, 2020)
Wolbachia is an iconic example of a successful intracellular bacterium. Despite its importance as a manipulator of invertebrate biology, its evolutionary dynamics have been poorly studied from a genomic viewpoint. To expand the number of Wolbachia genomes, we screen over 30,000 publicly available shotgun DNA sequencing samples from 500 hosts. By assembling over 1000 Wolbachia genomes, we provide a substantial increase in host representation. Our phylogenies based on both core-genome and gene content provide a robust reference for future studies, support new strains in model organisms, and reveal recent horizontal transfers amongst distantly related hosts. We find various instances of gene function gains and losses in different super-groups and in cytoplasmic incompatibility inducing strains. Our Wolbachia-host co-phylogenies indicate that horizontal transmission is widespread at the host intraspecific level and that there is no support for a general Wolbachia-mitochondrial synchronous divergence.